Influence of Ganoderma lucidum (Curt.: Fr.) P. Karst. on T-cell-mediated immunity in normal and immunosuppressed mice line CBA/Ca - Nizhenkovska, Iryna V; Pidchenko, Vitalii T; Bychkova, Nina G; Bisko, Nina A; Rodnichenko, Angela Y; Kozyko, Natalya O (Ceska a Slovenska farmacie, 2015)
The article presents the results of the investigation of the effect of biomass powder of the fungus Ganoderma lucidum on T-cell-mediated immunity in normal and immunosuppressed mice CBA/Ca. Delayed-type hypersensitivity assay was used. Experimental immunodeficiency was established with intraperitoneal injection of the immunosuppressant cyclophosphamide at a single dose of 150 mg/kg on the first day of the experiment. Results of the study show that the administration of biomass powder of Ganoderma lucidum in a dose of 0.5 mg/kg orally for 10 days increases the delayed-type hypersensitivity response in normal mice CBA/Ca. Administration of 0.5 mg/kg of biomass powder of the fungus Ganoderma lucidum for 10 days blocked the development of the T-cell-mediated immunosuppression, induced by administration of cyclophosphamide and restored the delayed-type hypersensitivity response in immunosuppressed mice. Key words: fungus Ganoderma lucidum cyclophosphamide immunodeficiency T-cell-mediated immunity delayed-type hypersensitivity.
Keywords: Animals; prášky, zásypy, pudry; Cyclophosphamide; Powders; Mice; pozdní přecitlivělost; reishi; Immunocompromised Host; T-lymfocyty; myši; Hypersensitivity, Delayed; Male; Mice, Inbred CBA; Reishi; imunokompromitovaný pacient; T-Lymphocytes; mužské pohlaví; zvířata; myši inbrední CBA; cyklofosfamid